How will independent prescribing affect wellbeing and career progression for the pharmacists of tomorrow? - Eugene Catangui (Future Healthcare Journal, 2024)
Pharmacist independent prescriber numbers continue to increase. In 2025/2026, independent prescribing will be integrated into the foundation year of pharmacy training, which will see a surge of pharmacists with the independent prescribing annotation on the General Pharmaceutical Council register. With increased responsibility and expectation from early careers pharmacists, the risk of burnout may be higher, and we could potentially see an increase in the number of individuals leaving the profession. In contrast, for those who remain in the pharmacy profession, there needs to be a fair evaluation of career progression, to ensure that they understand their skills are valued, and give them a reason to stay in the profession that they devoted years of their life to. As pharmacists are being upskilled, the lines between a pharmacist and physician may start to blur, but it should be noted that both professions have distinct roles in the treatment of a patient, and they are key members of the multidisciplinary team.